Probiotics administration alleviates cognitive impairment and circadian rhythm disturbance induced by sleep deprivation - Peijun Tian; Yunfei Hou; Zheng Wang; Jiaona Jiang; Xin Qian; Zhihao Qu; Jianxin Zhao; Gang Wang; Wei Chen (Food Science and Human Wellness)
Gut microbiome is indispensable for maintaining normal brain function. Specifically, gut microbiota plays a causal role in sleep deprivation (SD)-induced cognitive impairment. In this study, neurobehavioral effects of the Bifidobacterium breve strain (CCFM1025) were assessed in sleep-deprived mice. CCFM1025 improved the body weight and food and water intake of the mice. It also alleviated SD-induced cognitive behavioural abnormalities (in the novel object recognition test), but did not show beneficial effects on mood- and spatial memory-related behaviours. CCFM1025 significantly altered the gut microbial composition and genome function. Key microbial metabolites that may regulate sleep function were also identified, such as isovaleric acid and γ-aminobutyric acid in the gut and purine metabolites in the serum. Those metabolites may participate in gut-brain communication by acting on the striatal melatonin system, for example to increase melatonin levels, and by regulating the expression of circadian clock genes such as those encoding the adenosine A2A receptor and period circadian regulator 1. Collectively, administration of probiotics alleviated cognitive impairment and circadian rhythm disturbance induced by SD via modulation of gut microbiome and its metabolites. These findings may help guide the treatment of insomnia or other sleep disorders via dietary strategies.